A study on precipitation kinetics of sigma phase in a hot-rolled super duplex stainless steel during isothermal aging based on the Johnson–Mehl–Avrami model. (21st April 2017) - Ma, M.; Ding, H.; Misra, R. D. K.; Tang, Z. Y.; Li, H. B.; Fan, G. W.
Abstract : Isothermal aging treatment of 2507 super duplex stainless steel (SDSS2507) was conducted at 850°C after solution treatment at 1150°C. The characteristics of sigma (σ) precipitation kinetics in SDSS2507 were discussed and an improved JMA (Johnson–Mehl–Avrami) model had been developed. The results show that, the precipitation mechanism of σ phase in hot-rolled SDSS2507 was quite different to other ordinary DSSs. It can be found that σ phase precipitated via two mechanisms in this experiment. (1) The eutectoid decomposition δ → σ + γ2 . It dominated the precipitation kinetics of σ phase in aging 0–25 min, and at this time the volume fraction of σ phase increased rapidly. (2) After 25 min, the precipitation of σ phase absolutely relied on the transformation of γ → σ which is controlled by the diffusion of Mo and Ni in γ. In this period, the precipitation rate of σ phase was significantly decreased. In this case, the separate modeling on the basis of each transformation mechanism was adopted and then an improved JMA model was developed for the precipitation kinetics of σ phase in the whole aging process. As a result, a good agreement between the experimental data and this developed JMA model can be obtained.